Growth and learning in Mexican adults derived from the COVID-19 pandemic - Yazmín Alejandra Quintero Hernández; Perla Shiomara Del Carpio Ovando; Erika Robles Estrada (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The objective of this study is to know the difficul-ties faced, the ways to deal with them and the lear-ning acquired during the COVID-19 pandemic, for which a survey with three open questions was ap-plied, conveniently collected online from 387 Me-xican adults who were facing the pandemic during May 2020. A thematic analysis was carried out by categories of the responses, and it was found that the difficulties derived from the risks to health, economy, productivity and restrictions that the con-tingency implied. The coping strategies used were behavioral, directed towards solving the problem and to a lesser extent cognitive/emotional. The learning obtained implied the development of diverse skills and reflections. The results analyzed from Positive Psychology add evidence to the study of positive qualities and emotions to contribute to potentiate health and to the concept of crisis as a possibility of growth.